The contagion effect of collective voluntary turnover on firm performance and moderation of communication practices. (16th April 2021) - Chung, David Jinwoo; Kim, Andrea; Kim, Youngsang
Abstract: This study examines a moderated mediation model that delineates how collective voluntary turnover (CVT) impedes firms and when this organisational phenomenon is altered. Based on a social capital perspective, we propose that CVT can decrease firm performance over a long period through subsequent CVT, and communication practices weaken this negative mediational process. Analysing a three‐wave longitudinal dataset collected from 207 firms in South Korea, our work revealed that CVT decreased firm performance after 4 years via subsequent CVT, and such a contagion effect of CVT is mitigated among firms that extensively implemented communication practices. The results of this study provide insights into how, why, and when CVT damages firms by indicating its contagion effect over time and the buffer of communication practices. Also, our findings from South Korean firms broaden our understanding of the CVT‐consequence linkage in a non‐Western context.